2009
DOI: 10.1007/s10464-008-9222-8
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Organizational Change in Community‐Based Health and Human Services: From Tokenism to Political Engagement

Abstract: Community psychologists have long worked with community-based human service organizations to build participatory processes. These efforts largely aim at building participatory practices within the current individual-wellness paradigm of human services. To address collective wellness, human service organizations need to challenge their current paradigm, attend to the social justice needs of community, and engage community participation in a new way, and in doing so become more openly political. We use qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 33 publications
0
55
0
3
Order By: Relevance
“…A pesar del obstáculo que supone la inexistencia del derecho a voto para las personas migrantes, la apertura de espacios de participación social reales es una de las mejores herramientas con las que contamos para promover la integración de las personas y su bienestar (Bess et al, 2009). De esta manera, la intervención debe reconstruir el tejido social, lo que implica actuaciones en los diferentes niveles de análisis (Villasante, 1984):…”
Section: Participación Social Y Políticaunclassified
“…A pesar del obstáculo que supone la inexistencia del derecho a voto para las personas migrantes, la apertura de espacios de participación social reales es una de las mejores herramientas con las que contamos para promover la integración de las personas y su bienestar (Bess et al, 2009). De esta manera, la intervención debe reconstruir el tejido social, lo que implica actuaciones en los diferentes niveles de análisis (Villasante, 1984):…”
Section: Participación Social Y Políticaunclassified
“…Nonetheless, some studies (Bess et al, 2009;Mandel and Qazilbash, 2005;Wellens and Jegers, 2014) have shown the positive effects that beneficiary engagement can bring to the NPO to the beneficiaries involved in strategy and policy development, and to the beneficiaries as a stakeholder category. These positive outcomes include increased effectiveness of services, the better achievement of the NPO's goals, the strengthening of its legitimacy, the improvement of NPO board member commitment, organisational learning and growth, the increase of the organisation's social capital, and many other factors.…”
Section: Italian Banking Foundationsmentioning
confidence: 99%
“…To close the gap in health inequities, social inclusion through community participation is specifically identified as a strategy. Through shared power and inclusion in decisions that affect their lives, community members gain a voice and opportunities to make decisions in their best interest and that of their communities (Bess, Prilleltensky, Perkins, & Collins, 2009). …”
Section: Addressing Health Inequities Through Social Inclusionmentioning
confidence: 99%
“…Participation alone does not erase inequities in power and resources. Community members' participation is rendered inadequate in situations when they are given an opportunity to voice their opinions but are not given any decision-making power, resulting in tokenism rather than citizen power (Arnstein, 1969;Bess et al, 2009). In addition, whereas community organizations might be acting externally in accordance with concepts of inclusion, they might be reproducing organizational practices of inequity internally (Barros, 2010).…”
Section: Social Inclusion In Collective Actionmentioning
confidence: 99%